Mobile-Enhanced Outdoor Education for Tang Sancai Heritage Tourism: An Interactive Experiential Learning Approach - Jing Wang; Xing Zhang; Jasni Dolah (Education Sciences)
Outdoor experiences significantly enrich intangible cultural heritage tourism, yet limited interaction often restricts deep cultural learning. This research investigates how a mobile application, grounded in experiential learning theory, enhances tourists’ learning about Tang Sancai, a form of Chinese intangible cultural heritage, in the outdoor setting of Sancai Town, Luoyang. Employing a theory learning behavior design scenario framework, the application integrates activity-based exploration, reflective multimedia content, and immersive simulation scenarios to promote active participation, critical reflection, and context-rich outdoor learning experiences. Controlled experiments using pre- and post-tests and questionnaires revealed that participants using the application significantly outperformed those using conventional digital tools in knowledge retention, comprehension, and experiential learning outcomes. Technology acceptance analysis highlighted perceived usefulness as a critical driver of learning success. However, limited effects on behavioral progression suggest that short-term digital interactions may not sustain long-term behavioral change. This research offers a replicable mobile learning framework for outdoor cultural education, extends experiential learning theory to informal tourism contexts, and provides practical insights into using technology to enrich outdoor educational experiences, while supporting heritage preservation.